Economic partnership agreements between the European Union and African, Caribbean, and Pacific Countries: What is at stake for Senegal - Berisha-Krasniqi, Valdete; Bouët, Antoine; Mevel, Simon (International Food Policy Research Institute, 2008)
In recent years the European Union has sought to transform its trading regime with the ACP countries by advocating reciprocal free trade agreements with them through Economic Partnership Agreements (EPAs). As a result, the EPA talks were launched in 2002 and were expected be completed by the end of 2007. Nevertheless, many African countries, including Senegal did not reach agreements with the European Union in 2007 amid rising concerns that such agreements do not represent the interests of developing countries. This policy shift from preferential trade to free trade would imply drastic changes for Senegal?s economy, which currently enjoys relatively good access to European market (but also to the U.S. through the African Growth Opportunity Act) while applying a high domestic protection on all sources of imports. As a result, this type of reform would result in improved access to foreign markets only for the EU. Furthermore, the EPA implies a loss of tariff revenues from liberalization, which has been a key concern for ACP countries from the beginning of talks because they constitute a high level of public receipts there. Finally this kind of reform could lead to trade diversion in Senegal while creating not enough trade. Using the MIRAGE computable general equilibrium model the study examines the potential impact of Economic Partnership Agreements on ACP countries with a special focus on Senegal.